Assessment of consumption patterns for essential medicines: a study of the Nyeri county referral hospital - Murigi, Juliana W.; Ng'ethe, Henry; Nderitu, Douglas; Murigi, Veronica (International Journal of Research in Medical Sciences, 2021)
Background: Nyeri is one of the pilot Universal Health Coverage roll-out counties aimed at guaranteeing healthcare service access to all households in the region by 2022. The aim of the study was to provide management insights into ways of optimizing pharmaceutical management to ensure essential medicine are consumed by majority of population in need by 2022. Methods: A mixed-methods approach was used, combining quantitative and qualitative data collection techniques. Results: Amoxicillin had the highest (751,000) consumption over the study period. Other essential medicines with high consumption include paracetamol (432,000), metformin (280,264) and enalapril (111,800). The most cited reason for stock-outs was limited allocation of budget for medicines, a point that was mentioned by eight of the ten respondents. Conclusions: The study concludes that the stock-out frequency for essential medicines at the Nyeri County Referral Hospital is high. The frequent and persistent stock-out frequency for essential medicines is a problem considering the high consumption for essential medicines.